KECERDASAN EMOSIONAL DITINJAU DARI PERILAKU ALTRUISME PADA MAHASISWA JURUSAN KEPERAWATAN DI UNIVERSITAS RATU SAMBAN - Zuraida Zuraida (Jurnal Ilmiah Psyche, 2022)
Students majoring in nursing are prospective nurses whose job is to serve and assist in healing patients. So that prospective nurses must have high altruism behavior and be smart in understanding what other people feel which is called emotional intelligence. This study aims to examine the relationship between emotional intelligence and altruism behavior in nursing students. The variables of emotional intelligence and altruism behavior were measured using a scale. The subjects of this study amounted to 32 students majoring in nursing at Ratu Samban University. The sampling technique in this study used a probability sampling technique. The analytical technique used in this research is quantitative analysis using Karl Pearson's product moment with SPSS Version 20 for Windows. Based on the results of the study, it is known that emotional intelligence has a positive relationship with altruism behavior in nursing students at Ratu Samban University. There is a significant correlation (r0.893 with a significance <0.05) between the variable emotional intelligence and altruism behavior in nursing students, namely 0.000 and the significance value is below/smaller than 0.05, this means that the higher emotional intelligence, the higher the altruism behavior in students. students majoring in nursing on the contrary, the lower the emotional intelligence of students majoring in nursing, the lower the altruism behavior in students majoring in nursing. In nursing students, emotional intelligence has the most moderate level category with a contribution of 44% and altruism behavior has the most moderate level category with 53% contribution.